(untitled) (Innovaciones Educativas, 2023)
Literacy practices are constantly changing in the digital era. This paper presents a systematic review that analyzes the state of research in the last eleven years (2010-2021) in Latin America and North America regarding teacher training in literacy at a Higher Secondary Education (HSE) level. The PRISMA protocol was followed, and inclusion and exclusion criteria were established, along with research in both closed and open databases such as ERIC, Academic Search, Dialnet, among others. Results show that among the training needs of HSE teachers, there should be an emphasis on developing generic teaching skills such as communication skills and the use of Information and Communication Technologies (ICT). In training courses, promoting personal reading stands out as an act of self-reflection and for building reading identities; with equal importance, spaces for dialogue were detected to promote collaborative work between teachers that overcomes an individualistic vision in teaching. It is concluded that it is essential to consider in the area of training the emerging platforms and the new formats of the reading and writing practices of the 21st century to integrate them within the scope of the school and motivate the development of this competence at the HSE level.